Regional state funds for support of science, technology and innovation: success, problems, foreign experience - Lapochkina VV; Kamensky AS; Kornilov AM (Zenodo, 2018)
This article examines the activities of the regional state funds for support of science, technology and innovation as an instrument for implementing regional innovation policy, with the aim to develop recommendations for stimulating and enhancing the efectiveness of research and innovation in the subjects of the Russian Federation. The authors faced several tasks: to ind out whether the regional scientiic funds take into account the speciics of their region (its social, economic, technological problems) when forming the tenders; to clarify whether there is a competition with federal funds, as well as to study the public opinion on the activities of the regional state funds drawing on the reviews from sites, forums and social media. The authors analyzed the foreign experience of forming a regional network of state scientiic foundations in order to identify the most relevant and successful examples of such activities, applicable in Russian conditions. On the basis of this research the authors outlined some proposals for the development of a network of the regional funds for science, technology and innovation in order to increase the eiciency of the regional budgetary expenditures for scientiic research, which should create favorable conditions for research and development in accordance with modern principles of organization of innovation activities, as well as contribute to the solution of the critical regional problems. : For citation: LAPOCHKINA, V. V., KAMENSKY, A. S., KORNILOV, A. M. (2018) Regional state funds for support of science, technology and innovation: success, problems, foreign experience. Science. Innovations. Education. No. 2 (28). Pp. 26–53. : {"references": ["Statistical form 2-Science \u00abInformation on the implementation of research and development\u00bb. Federal Service of State Statistics [oicial website]. URL: http://www.gks.ru (Accessed: 25 January 2013).", "PLIEVA, Z. R., ODINTSOVA, N. N. Analysis of the main mechanisms for the implementation of the government science, technology and innovation policies in the subjects of the Russian Federation. Innovatics and Expert Examination. Moscow: FGBNU SRI FRCEC, 2015. No. 1 (14). Pp. 124\u2013133.", "GLISIN, F. F., KALYUZHNY, V. V., LEBEDEV, K. V. Analysis of the inancing of science from regional budgets. Innovations. 2014. No. 3 (185). Pp. 33\u201341.", "Report on the implementation of the consolidated budget of the constituent entity of the Russian Federation. Federal Treasury [oicial website]. URL: http://www.roskazna.ru/ispolnenie- byudzhetov/konsolidirovannye-byudzhety-subektov. (Accessed: 29 January 2018).", "Meeting of the Council for Science and Education. Kremlin.ru. URL: http://kremlin.ru/events/president/news/16726 (Accessed: 2 May 2018).", "Report of the Krasnoyarsk Regional Fund for Support of Scientiic and Technical Activity. Krasnoyarsk Regional Fund for Support of Scientiic and Technical Activity [oicial website]. URL:http://www.sf-kras.ru/wp-content/uploads/2017/06/ Publichnyiy-otchet-_rukovoditelya_2016_26.06.2017_.pdf (Accessed: 5 February 2018).", "Strategy of innovative development of the Novosibirsk region up to 2030. Ministry of Education, Science and Innovation Policy of the Novosibirsk Region [oicial website]. URL: https://minobr. nso.ru/page/5415 (Accessed: 9 February 2018).", "The results of the contest for granting subsidies to the innovators for preparation, transfer and commercialization of technologies, including the production of a pilot batch of products, its certiication, production modernization and other measures, were summarized. Novosibirsk Regional Innovation Fund [oicial website]. URL: https://fondnid.ru/blog/2016/11/11/podvedeny-itogi-konkursa- na-predostavlenii-subsidij-subektam-innovatsionnoj-deyatelnosti- na-podgotovku-osushhestvlenie-transfera-i-kommertsializatsiyu- tehnologij-vklyuchaya-vypusk-opytnoj-partii-produ / (Accessed: 9 February 2018).", "About the fund. Fund for young scientists of the Republic of Sakha (Yakutia) (NOFMU) [oicial website]. URL: http://nofmu. ru/?p=233 (Accessed: 10 February 2018).", "NOFMU announces the call for applications for the ''Academic Mobility'' contest. Fund for young scientists of the Republic of Sakha (Yakutia) (NOFMU) [oicial website]. URL: http:// nofmu.ru/?p=324 (Accessed: 10 February 2018).", "NOFMU announces the call for applications for the ''Scientiic events'' contest. Fund for young scientists of the Republic of Sakha (Yakutia) (NOFMU) [oicial website]. URL: http://nofmu. ru/?p=321 (Accessed: 10 February 2018).", "About the fund. Investment and Venture Fund of the Republic of Tatarstan [oicial website]. URL: http://www.ivfrt.ru/about/ (Accessed: 5 February 2018).", "Venture Fund of the Republic of Bashkortostan [oicial website]. URL: https://vfrb.ru/ (Accessed: 7 February 2018).", "Livejournal.com. URL: https://ascir.livejournal.com/702310.html (Accessed: 7 February 2018).", "''You know, I have your application'': the head of the RSF about the examination of grants. Indicator.ru, 16.05.2017. URL: https:// indicator.ru/article/2017/05/16/rnf-hlunov-ekspertiza/ (Accessed: 7 February 2018).", "Ministry of Science and Technology, Government of India. State Science & Technology Programme [oicial website]. URL: http://www.dst.gov.in/scientific-programmes/st-and-socio- economic-development/state-science-technology-programme (Accessed: 11 February 2018).", "Council of Science and Technology, U.P. General Information and Guidelines for Award of Research-Assistantship and Grant-in-aid. Regulation \u2013 1988 (As Amended to Time, 2015) [oicial website]. URL: http://www.dstup.gov.in/Application// uploadDocuments/Content/ R__D_Guidelines.pdf (Accessed: 12 February 2018)", "Department of Science and Technology, Government of Uttar Pradesh. Programmes of State S&T Council [oicial website]. URL: http://dstup.in/content/66 (Accessed: 12 February 2018).", "S\u00e3o Paulo Research Foundation, FAPESP [oicial website]. URL: http://www.fapesp.br/en (Accessed: 13 February 2018).", "Steinbeis STW. Steinbeis 1983\u20132008 [oicial website]. URL: http://www.scmt.com/ileadmin/Dokumente/Zentrale/Steinbeis_ 1983_-_2008_en.pdf (Accessed: 13 February 2018).", "Canadian Encyclopedia. Ontario Research Foundation [oicial website]. URL: https://www.thecanadianencyclopedia.com/en/ article/ontario-research-foundation/ (Accessed: 13 February 2018).", "Statistics Canada. Gross domestic expenditures on research and development (GERD), by funding sector, by province (Canada) [oicial website]. URL: http://www.statcan.gc.ca/tables-tableaux/ sum-som/l01/cst01/scte01a-eng.htm (Accessed: 14 February 2018).", "California Council on Science and Technology [oicial website]. URL: http://ccst.us/about.php (Accessed: 14 February 2018)."]}